Hadean age for a post-magma-ocean zircon confirmed by atom-probe tomography - Valley, J.; Cavosie, A.; Ushikubo, T.; Reinhard, D.A.; Lawrence, D.; Larson, D.J.; Clifton, P.; Kelly, T.; Wilde, Simon; Moser, D.; Spicuzza, M.J. (Nature Publishing Group, Macmillan Publishers Ltd, 2014)
The only physical evidence from the earliest phases of Earth’s evolution comes from zircons, ancient mineral grains that can be dated using the U–Th–Pb geochronometer1. Oxygen isotope ratios from such zircons have been used to infer when the hydrosphere and conditions habitable to life were established2, 3. Chemical homogenization of Earth’s crust and the existence of a magma ocean have not been dated directly, but must have occurred earlier4. However, the accuracy of the U–Pb zircon ages can plausibly be biased by poorly understood processes of intracrystalline Pb mobility5, 6, 7. Here we use atom-probe tomography8 to identify and map individual atoms in the oldest concordant grain from Earth, a 4.4-Gyr-old Hadean zircon with a high-temperature overgrowth that formed about 1 Gyr after the mineral’s core. Isolated nanoclusters, measuring about 10 nm and spaced 10–50 nm apart, are enriched in incompatible elements including radiogenic Pb with unusually high 207Pb/206Pb ratios. We demonstrate that the length scales of these clusters make U–Pb age biasing impossible, and that they formed during the later reheating event. Our tomography data thereby confirm that any mixing event of the silicate Earth must have occurred before 4.4 Gyr ago, consistent with magma ocean formation by an early moon-forming impact4 about 4.5 Gyr ago.